2016
DOI: 10.3892/mmr.2016.6037
|View full text |Cite
|
Sign up to set email alerts
|

Fas expression is downregulated in gastric cancer

Abstract: The aim of the present study was to investigate Fas expression in tumor samples from patients with gastric cancer, in order to determine the involvement of the Fas signaling pathway. The protein expression levels of Fas, caspase-8, caspase-3 and poly (adenosine diphosphate-ribose) polymerase 1 (PARP1) were examined in gastric cancer specimens and their associations with clinical pathological parameters were analyzed with immunohistochemical staining and western blot analysis. The mRNA expression was quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…In addition, the present work indicates that the percentages of neurons in the MPs expressing CASP8 decreased in the cancer-affected stomach wall. The decreased expression of CASP8 is in accordance with the study of Wang et al [ 22 ] that was performed on gastric cancer tissue and cells. This phenomenon was not observed in previous studies including patients with CRC [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the present work indicates that the percentages of neurons in the MPs expressing CASP8 decreased in the cancer-affected stomach wall. The decreased expression of CASP8 is in accordance with the study of Wang et al [ 22 ] that was performed on gastric cancer tissue and cells. This phenomenon was not observed in previous studies including patients with CRC [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
“…It is difficult to explain this phenomenon, because in the available literature there is a lack of detailed data concerning the chemical coding of neurons localized in MPs. In reference to CASP3, it has only been found that in the gastric cancer, the expression of this protein was significantly lower compared to corresponding healthy tissue [ 21 , 22 ]. This difference is perhaps due to the fact that present study focuses the analysis of chemical coding of neurons in the MPs but not expression of these enzymes inside gastric cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-8 is an important apoptosis-related gene, and its abnormal expression is closely associated with carcinogenesis (45). Previous studies have already demonstrated decreased caspase-8 expression in various types of cancers (34,46). Consistently, the results of the current study also found that caspase-8 mRNA and protein expression levels in OSCC were reduced, and further demonstrated a positive correlation between PER2 and caspase-8.…”
Section: Per2 Expressionsupporting
confidence: 90%
“…Yang et al ( 37 ) reported that Fas signaling facilitated GC metastasis. Wang et al ( 38 ) found that the expression of Fas was downregulated in GC, and that CASP8 was associated with outcome in patients with GC. These findings suggest that JAK2, CASP8 and Fas are involved in the pathogenesis of GC.…”
Section: Discussionmentioning
confidence: 99%